Desain Pembelajaran Eksponen Negatif menggunakan Konteks “Grid Images” Dengan Pendekatan PMRI - Tiara Patria Ningsih; Zulkardi; Ely Susanti; Meryansumayeka (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study aims to develop and validate a learning design for negative exponent material using the context of “grid images” through the Indonesian Realistic Mathematics Education (PMRI) approach at a public high school in Palembang. The background of this study stems from students' difficulties in learning and understanding the concept of negative exponents, which is abstract and not closely related to its visual form. Through the PMRI approach, mathematics learning becomes more meaningful and profound because students learn mathematics from contexts that are close to their lives. The research method used is design research, which includes three main stages, namely preliminary design, teaching experiment, and retrospective analysis. The research subjects were tenth-grade students at a public high school in Palembang. Data were collected through observation, interviews, documentation, and student work, then analyzed descriptively and qualitatively to evaluate the learning process and outcomes. The results showed that the use of visual forms in the form of “grid images” and the PMRI approach could help students understand the meaning of negative exponents and find the formal form of negative exponents. In addition, the PMRI approach created a more interactive learning atmosphere between students and with teachers and helped students understand and find the formal form of negative exponents themselves. Thus, this learning design became an innovative alternative in teaching negative exponent material.